Effect of methylisothiazolinone biocide in tissue culture sterilization of Casuarina equisetifolia. Issue 1 (June 2020) - Putri, A I; Prastyono; Haryjanto, L; Herawan, T; Fauzi, A; Izudin, E; Setiawan, A; Suprihati; Hartono, R; Priatna, D; Herdiantara, B; Suharyanto; et al.
Abstract: In this study, modification of tissue culture sterilization techniques using methylisothiazolinone bocide (MB) in liquid and solid medium was used to evaluate the acquisition of axenic Casuarina equisetifolia culture in vitro with natureexplant sources. One experimental unit had 12treatment combinations with 20replications of explants in each treatment. Acquisition of the best axenic culture of C. equisetifolia after 30 days of incubation was in a sterilization combination for 3 days shaking out in liquid WPM medium with 8 mg/l MBand in solid WPM medium with 6 mg/l MB. C. equisetifoliashowsa good growth response in WPM medium without the addition of exogenous growth hormone. The first indication of axillary shoot explants were elongation response within 15 days of culture initiation. Shoot tips changed in color from dark green to a more obvious transparent green and the internode sections became swollen and barrel-shaped. Single shoot formation from axillary buds at basal nodes and sprouted lateral buds were visible within 30 days. The 90%of shoot formation in the axenic culture of Casuarina equisetifolia werefrom lateral buds.